DEK1; missing piece in puzzle of plant development. (February 2015) - Olsen, Odd-Arne; Perroud, Pierre-François; Johansen, Wenche; Demko, Viktor
<x xml:space="preserve">Abstract</x> Patterning of land plant bodies is determined by positioning of cell walls. A crucial event in land plant evolution was the ability to utilize spatial information to direct cell wall deposition. Recent studies of DEK1 in Physcomitrella patens support a role for DEK1 in position dependent cell wall orientation.